Model Komunikasi Relasional Digital CT ARSA Foundation sebagai Mekanisme Pembentukan Kepercayaan Stakeholder di Era Filantropi Digital - Eka Abraham; Nurul Hidayat; Edison Bonar Tua Hutapea (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Digital communication transformation has changed the way philanthropic organizations build relationships with stakeholders. Organizations can no longer rely solely on institutional reputation and formal publications, but are required to present transparent, interactive, and long-term relationship-oriented communication to build public trust. This study aims to analyze the digital relational communication model of CT ARSA Foundation as a mechanism for building stakeholder trust in the era of digital philanthropy. This research employed a qualitative approach using a descriptive-critical literature review method through the analysis of scientific journals, academic books, and previous studies relevant to organizational communication, stakeholder trust, nonprofit communication, and digital engagement. The findings indicate that CT ARSA Foundation’s digital relational communication model is constructed through three main components: digital information transparency that builds rational trust, humanitarian storytelling that develops emotional trust, and participatory interaction that encourages stakeholder engagement. The integration of these three components forms a trust-based communication mechanism that strengthens social legitimacy, public loyalty, and organizational sustainability. This study confirms that digital relational communication is a strategic element for philanthropic organizations in establishing sustainable relationships with stakeholders in the digital era.